We, the sovereign - Baiocchi, Gianpaolo (Radical futures, 2018)
In this book, Gianpaolo Baiocchi argues that the 'people' who rule must be understood as a demos that is totally open, inclusive and egalitarian. But sovereignty must also be absolute. Baiocchi's provocative vision will be essential reading for all activists who want to understand the true meaning of radical democracy in the 21st century.